Design of quarter-wavelength resonator filters with coupling controllable paths - Meng, Fanyi (2013)
This paper presents compact quarter-wavelength resonator filters to have multiple transmission zeros points (ZPs) with controllable electric and magnetic coupling paths. For two coupled resonators, the relative strength of electric and magnetic coupling paths determines the transmission ZPs positions that can be at either lower or upper stopband. Besides, the location of transmission ZPs can be precisely controlled by tuning the dimension parameters. Based on the proposed topology and configuration, the second-order and fourth-order bandpass filters operating at 5.1 GHz have been designed using multi-layer LTCC technology.